تحليل تعليم المفردات في مادة اللغة العربية لدى التلاميذ في المدرسة الإبتدائية الإسلامية النموذجية فنجابونجان - Denggan Hayani Ritonga; Isra Hayati Darman; Ria Rafita Supriani (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study aims to determine the implementation, obstacles and solutions in learning Arabic vocabulary for students of MI Model Panyabungan. The method chosen by the researcher in this research plan is a qualitative research method. The results obtained are the methods used are imitating and memorizing, the strategies used are playing and singing during learning, and the media used are blackboards and language games to increase students' interest in learning vocabulary. The problems faced by fifth grade students of SD Model Islam Fangabungan are the lack of reading books that support students' fluency in speaking Arabic and excessive memorization of vocabulary so that students feel bored when learning Arabic. The solution is that teachers must be more enthusiastic in providing motivation and support to students, teachers give prizes, teachers are lenient with students according to students' abilities in memorizing vocabulary, completing books in the library including Arabic books.